Risk analysis, regulation proposal and technical guide for pilot tests of hydrogen vehicles in underground mining. (19th May 2022) - Sánchez-Squella, Antonio; Fernández, Daniel; Benavides, Rodrigo; Saldias, Javier
Abstract: Safety related issues, regarding the use of hydrogen technologies have raised great concern in the industry, especially in mining, due to confined places where hydrogen leaks can accumulate and eventually cause a fire hazard or explosion. Currently, there are no sufficiently robust regulations or experiences regarding the use of hydrogen in mining, which must be resolved to design safety models, pertinent regulations and a strategy to guide the use of hydrogen. This article qualitatively and quantitatively analyzes the risks of a HFCV pilot project, identifying these risks to determine how they are involved in mining operations and evaluates how dangerous these are in this environment. This is achieved through a HAZOP study and using the F&EI, where the results contribute to the knowledge of hydrogen technologies. One of the strongest results obtained by using the F&EI, shows that a vehicle fueled by hydrogen (5 kg at 700 bar) in full operation presents an index of 153.0, a vehicle of similar characteristics fueled with natural gas (20 kg at 200 bar) will present a value of 197.1. Therefore, if the use of natural gas is authorized in underground mining, hydrogen that can be an even safer alternative, should be authorized too. Moreover, the results show that there is a similar probability with diesel (60 kg at 1 bar) of causing a potential incident, in addition, the HAZOP indicates that as long as hydrogen leaks are kept under control with adequate ventilation and appropriate vehicle design, the system becomes even more robust, which would be achieved by including additional infrastructure security measures to mitigate events of fire and explosion. Highlights: HAZOP is an inductive risk identification technique based on the premise that accidents occur due to a process deviation. The Fire and Explosion Index (F&EI) quantify the potential fire and explosion risk of a process unit and its content. Regarding F&EI risk, while vehicles are in operation, NG displayed an index value of 197.1, surpassing the H2 value of 153.0